FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TAX AVOIDANCE - Abdul Karim (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
This research aims to determine the effect of audit committees,institutional ownership, independent commissioners, size, leverage andprofitability (ROA) to tax avoidance. Dependent variables used inthis study are tax avoidance and Independent Variables used in thisstudy are audit committee, institutional ownership, proportion ofindependent commissioner, size, laverage and profitabiliatas (ROA). Thepopulation in this study are all manufacturing companies listed on theIndonesia Stock Exchange in 2011-2015. The sample selection usingpurposive sampling method with final sample 18 observation data duringthe period of 2011-2015. The type of data used is secondary data taken fromCompany Financial Statement and Company Annual Report. Data analysistechnique used in this research is multiple linear regression analysistechnique with SPSS 20 program application. The results showed that thevariable of institutional ownership, size and profitability (ROA) have aneffect on tax avoidance. While the audit committee, the proportion ofindependent commissioners and laverage have no effect on tax avoidance.The coefficient of determination in this research is 35.8%. Further researchis expected to add the number of samples, extend the study period and addother variables that affect Tax Avoidance such as audit quality for betterresearch results.